Dialogism or Interconnectedness in the Work of Louise Erdrich. - Lysik, Marta J. (Cambridge Scholars Publishing : Cambridge Scholars Publishing, 2017)
This study portrays how Louise Erdrich's writing extends Bakhtin's concepts of dialogism and the novel through an investigation of a selection of her works, as well as her practices of writing, co-writing, re-writing, and reading novels. Erdrich's hallmark dialogic literary style and practice encompasses writing a series of books; re-cycling protagonists, narrators, events, themes and settings; re-writing previously published novels; employing heteroglossia and polyglossia; co-authoring texts, blogging about books; translating different epistemologies for different audiences; and spotlighting.